Neonatal stress-induced affective changes in adolescent Wistar rats: early signs of schizophrenia-like behavior - Girardi, Carlos Eduardo Neves; Zanta, Natália Cristina; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2014)
Psychiatric disorders are multifactorial diseases with etiology that may involve genetic factors, early life environment and stressful life events. The neurodevelopmental hypothesis of schizophrenia is based on a wealth of data on increased vulnerability in individuals exposed to insults during the perinatal period. Maternal deprivation disinhibits the adrenocortical response to stress in neonatal rats and has been used as an animal model of schizophrenia. To test if long-term affective consequences of early life stress were influenced by maternal presence, we submitted 10-day old rats, either deprived (for 22 h) or not from their dams, to a stress challenge (i.p. saline injection). Corticosterone plasma levels were measured 2 h after the challenge, whereas another subgroup was assessed for behavior in the open field, elevated plus maze, social investigation and the negative contrast sucrose consumption test in adolescence (postnatal day 45). Maternally deprived rats exhibited increased plasma corticosterone levels which were higher in maternally deprived and stress challenged pups. Social investigation was impaired in maternally deprived rats only, while saline injection, independently of maternal deprivation, was associated with increased anxiety-like behavior in the elevated plus maze and an impaired intake decrement in the negative sucrose contrast. In the open field, center exploration was reduced in all maternally-deprived adolescents and in control rats challenged with saline injection. The most striking finding was that exposure to a stressful stimulus per se, regardless of maternal deprivation, was linked to differential emotional consequences. We therefore propose that besides being a well-known and validated model of schizophrenia in adult rats, the maternal deprivation paradigm could be extended to model early signs of psychiatric dysfunction, and would particularly be a useful tool to detect early signs that resemble schizophrenia.